What is special about the human brain? - Passingham, R. E. 1943-; Oxford scholarship online (Online service). (Oxford Oxford University Press, 2008)
The mental gap between man and ape is immense. As the brain is the organ of the mind, we must assume that throughout evolution there were changes in the brain that created this gap. This book is a search for those changes. Written in a lively style, the book is a far-reaching and exciting quest for those things that make humans unique.
Includes bibliographical references and index.
Keywords: Comparative neurobiology; Neuropsychology; Primates -- Physiology; Brain -- Imaging; Electronic books